Determinant of Eï¬€ective Family Communication among First-Grade High School Adolescents Aged 15 - 16 Years: A Multi-Centre Cross-sectional Study - Heni Dwi Windarwati; Retno Lestari; Ridhoyanti Hidayah; Ahmad Afif Supianto; Satrio Agung Wicaksono; Niken Asih Laras Ati; Mira Wahyu Kusumawati; Dewa Ayu Anggi Gharbelasari; Ridwan Sofian; Phat Prapawichar (JKP (Jurnal Keperawatan Padjajaran), 2022)
Background: Family communication can become a support system for adolescents. Ineï¬€ective communication in the family causes emotional problems and poor psychological well-being in adolescents.